The effect of coordination environment on the activity and selectivity of single-atom catalysts - Zhang, Yuqi; Yang, Jack; Ge, Riyue; Zhang, Jiujun; Cairney, Julie M.; Li, Ying; Zhu, Mingyuan; Li, Sean; Li, Wenxian (Coordination chemistry reviews, 2022)
[Display omitted] •Coordination environments of single-atom catalysts (SACs) are highlighted.•Coordination environments explain the structure-performance relationship rationally.•Suitable binding states and electronic interactions stabilize and functionalize SACs.•Preparation methods significantly affect the coordination environments of SACs.•Advanced characterizations reveal the geometric and electronic structures of SACs. Traditional heterogeneous catalysts with noble metals as active sites only have surface-active substances involved in the catalytic reactions, which greatly reduces the material utilization efficiencies and increases the production costs. Since 2011, single-atom catalysts (SACs) have been proven useful to solve this problem and have become a rapidly evolving research field. SACs allow the benefits from both homogeneous and heterogeneous catalysts to be combined in a single system, by providing isolated active sites, high selectivity, and ease of separation from reaction systems. Unfortunately, SACs suffer from the agglomeration of metal atoms during the fabrication and application processes for their high surface energy. Nevertheless, this problem can be solved by constructing strong coordination bonds between single-atoms and their supports, which can also significantly influence the activity and selectivity of SACs. In order to further identify and regulate the coordination environments of single-atoms, it is critical for the structural, physical, and chemical properties of SACs to be characterized downward to the atomic level. Hence, we first review different physical and chemical strategies used to stabilize the single-atom environments and clarify how the obtained coordination environments affect the catalytic performance of SACs. The reasonable selection of preparation methods can meet the specific requirements of central atoms and/or coordinated atoms, and effectively prevent the agglomeration of single-atoms. Moreover, we review the state-of-art complementary characterization methods (ex-situ and in-situ) to deepen the understanding of the critical structure–property relationship for SACs, which is essential to promote the rational design of SACs and other heterogeneous catalysts. Finally, we summarize several stages for the development of SACs and highlights challenges and prospects for the future of this field from the perspective of coordination environments. We believe that this review will provide new insights for future research on SACs to further improve both their activities and stabilities, reduce the associated preparation costs, and realize large-scale industrial applications.